2019
DOI: 10.1111/gwao.12362
|View full text |Cite
|
Sign up to set email alerts
|

Who cares? A lack of self‐care for women in the non‐profit/non‐governmental sector

Abstract: In this article I examine the lack of self‐care regimes for women working in the non‐profit/non‐governmental sector. While I draw on ethnographic research conducted in the Malaysian context of women's organizations, the issue of self‐care for activists and feminist activists is a global one that crosses borders and boundaries. I explore the gendered nature of care and care professions to demonstrate how women are predominantly affected in these working environments. To date, there has been little scholarship o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…One ED pointedly stated, “... one of the things that we know about COVID is that women-identified folks are disproportionately impacted by [the pandemic]...” (FG203, T1). Given our sample consisted of mostly female-identified people, and this reflects the make-up of primarily female-identified clients and workers in this field ( Bandali, 2019 ; Nordhues et al, 2021 ), the narratives below represent the experiences of women (shelter clients, frontline service providers, and EDs) during the pandemic, though men's perspectives are included where available.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One ED pointedly stated, “... one of the things that we know about COVID is that women-identified folks are disproportionately impacted by [the pandemic]...” (FG203, T1). Given our sample consisted of mostly female-identified people, and this reflects the make-up of primarily female-identified clients and workers in this field ( Bandali, 2019 ; Nordhues et al, 2021 ), the narratives below represent the experiences of women (shelter clients, frontline service providers, and EDs) during the pandemic, though men's perspectives are included where available.…”
Section: Resultsmentioning
confidence: 99%
“…These expectations disproportionately fell on the shoulders of women, especially single mothers, those who had little to no informal support, or those who were unable to access childcare services. It has been clearly demonstrated that women tend to take on more of the parenting and caregiving responsibilities in the home due to gender stereotypes and norms that situate women as nurturing, caring, and self-sacrificing ( Bandali, 2019 ; Moyser & Burlock, 2018 ) and that this trend continued during the pandemic when parenting and caregiving responsibilities were more complex ( Gladu, 2021 ; Hazarika & Das, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And both Hélène and Marthe went through periods of extreme working hours (70–80 h/week) which through the exceptional conditions of the crisis became further normalized by their organizations (Turnbull & Wass, 2015). Lastly, for Pauline self‐sacrifice became key (Bandali, 2020) as she took on extreme amounts of caring work, both for her family and pupils, all combined in the private sphere of the home in which she struggled to find a ‘room of her own’ (Woolf, 2015).…”
Section: Discussionmentioning
confidence: 99%